United Nations World Crime Surveys: Fifth Survey, 1990-1994 ([Verlag nicht ermittelbar], 2003)
The Fifth United Nations Survey, covering the years 1990-1994, was designed to collect data on the incidence of reported crime and the operation of criminal justice systems with a view to improving the dissemination of that information globally. To that end, the survey facilitates an overview of trends and interrelationships among various parts of the criminal justice system to promote informed decision-making in its administration, nationally and crossnationally. Variables describe combined police and prosecution expenditure by year and by country, number of police personnel by gender, total number of homicides by country and by city, number of assaults, rapes, robberies, thefts, burglaries, frauds, and embezzlements, amount of drug crime, number of people formally charged with crime, age of suspects, number and gender of prosecutors, number of individuals prosecuted and the types of crimes prosecuted, gender and age of individuals prosecuted, types of courts, number of individuals convicted and acquitted, numbers sentenced to capital punishment and various other punishments, number of convictions on various charges, number of individuals sentenced and in detention, number of prisoners, sentence lengths, and prison demographics.